Changes needed to medicine in the United Kingdom before senior UK-trained doctors, working outside the UK, will return: questionnaire surveys undertaken between 2004 and 2015 - Lambert, T; Smith, F; Goldacre, M (SAGE Publications, 2017)
Objective To report the changes to United Kingdom (UK) medicine which doctors who have emigrated tell us would increase their likelihood of returning to a career in UK medicine. Design Questionnaire survey. Setting UK-trained medical graduates. Participants Questionnaires were sent 11 years after graduation to 7,158 doctors who qualified in 1993 and 1996 in the UK: 4,763 questionnaires were returned. Questionnaires were sent 17 and 19 years after graduation to the same cohorts: 4,554 questionnaires were returned. Main outcome measures Comments from doctors working abroad about changes needed to UK medicine before they would return. Results Eleven years after graduation, 290 (6%) of respondents were working in medicine abroad; 277 (6%) were doing so 17/19 years after graduation. Eleven years after graduation, 53% of doctors working abroad indicated that they did not intend to return, and 71% did so 17/19 years after graduation. These respondents reported a number of changes which would need to be made to UK medicine in order to increase the likelihood of them returning. The most frequently mentioned changes cited concerned ‘politics/management/funding’, ‘pay/pension’, ‘posts/security/opportunities’, ‘working conditions/hours’, and ‘factors outside medicine’. Conclusions Policy attention to factors including funding, pay, management and particularly the clinical-political interface, working hours, and work-life balance may pay dividends for all, both in terms of persuading some established doctors to return and perhaps more importantly, encouraging other, younger doctors, to believe that the UK and the NHS can offer them a satisfying and rewarding career.